Mapping the website and mobile app audiences of Russia’s foreign communication outlets, RT and Sputnik, across 21 countries - Kling, J; Toepfl, F; Thurman, N; Fletcher, R (Shorenstein Center on Media, Politics and Public Policy, Harvard Kennedy School, 2022)
Following Russia’s invasion of Ukraine, policymakers worldwide have taken measures to curb the reach of Russia’s foreign communication outlets, RT and Sputnik. Mapping the audiences of these outlets in 21 countries, we show that in the quarter before the invasion, at least via their official websites and mobile apps, neither outlet reached more than 5% of the digital populations of any of these countries each month. Averaged across all countries, both outlets’ website and mobile app reach remained approximately constant between 2019 and 2021, was higher for men, and increased with audiences’ age.